Women's education in the fertility transition: The reversal of the relationship between women's education and birth spacing in Indonesia - Jungho Kim (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2005)
It is generally thought that both the demand for children and the cost of fertility control are major forces in fertility decline. Most researchers find that family planning programs in developing countries, which lower the cost of fertility control, play a small role in the fertility transition relative to other economic factors that affect the demand for children. This paper examines one aspect of fertility, namely the second birth interval in Indonesia over the period 1970 to 1993. It is observed that higher female education is associated with a shorter birth interval among earlier cohorts, but with a longer birth interval among later cohorts. The finding is that changes in the effect of education on birth hazard over time are primarily driven by changes in the cost of fertility control rather than through changes in the demand for children. Hence, family planning programs can have a big impact on fertility in a relatively low-educated population. In addition, in the context of contraceptive technology, the result can be interpreted as evidence for the hypothesis that education enhances the ability to decipher new information.
Keywords: J13; J24; 330; Birth Spacing; Female Education; Family Planning Programs and Indonesia; Fertilität; Familienplanung; Frauen; Bildungsniveau; Indonesien